The effect of finite mass in cavity-QED calculations - Ankita Nair; Vikas Bharti; Yetmgeta S. Aklilu; Kálmán Varga (AIP Advances)
The effect of finite nuclear mass is investigated in coupled light–matter systems in cavity quantum electrodynamics using the Pauli–Fierz Hamiltonian. Three different systems, the He atom, the H− ion, and the H2+ ion, are investigated. There are small but significant differences in the behavior of the binding energies as a function of coupling strength. The probability of coupling to light is found to be very small, but even this small coupling has a very strong effect on the energies of the systems.